Liveable streets in Hanoi: A principal component analysis. (October 2015) - Sanders, Peter; Zuidgeest, Mark; Geurs, Karst
Abstract: Liveability along four streets in Hanoi, Vietnam is assessed. Hanoi is a rapidly growing metropolis characterised by high levels of personal motorized traffic. Two high traffic volume streets and two low traffic volume streets were studied using a mixed methods approach, combining the collection and analysis of quantitative and qualitative data on traffic volumes and liveability perceptions of its residents. The research methodology for this study revisits part of the well-known Liveable Streets study for San Francisco by Appleyard et al. (1981). A Principal Component Analysis (PCA) shows that residents on both low traffic volume streets experience less traffic hazard and stress, including noise and air pollution, than neighbouring high traffic volume streets. In line with Appleyard, the study shows that low traffic volume streets were rated more liveable than high traffic volume streets. In contrast to Appleyard, however, the study also shows that traffic volumes are not correlated with social interaction, feeling of privacy and sense of home, which is likely caused by the high levels of collectivism typical for Vietnam. Finally, the study indicates a strong residential neighbourhood type dissonance, where a mismatch exists between preferences for living in peaceful and quiet streets and the actual home location of residents. Highlights: Liveability of residents along four streets with different traffic levels in Hanoi is studied. A principal component analysis (PCA) is used to identify liveability constructs. Liveability constructs are correlated to traffic volumes along four different streets in Hanoi. Low traffic volume streets were rated more liveable than high traffic volume streets. Traffic volumes seem less correlated with social interaction and home territory due to high collectivism.